Satisficing in sales competition: experimental evidence - Siegfried Berninghaus; Werner Güth; M. Vittoria Levati; Jianying Qiu (University of Innsbruck, Department of Public Finance, 2009)
In a duopoly market, aspiration levels express how much sellers want to earn given their expectations about the other's behavior. We augment the sellers' decision task by eliciting their profit aspiration. In a first experimental phase, whenever satisficing is not possible, sales choices, point beliefs, or aspiration levels have to be adapted. This allows us to investigate which of these three aspects individuals revise more often. In a second phase, testing the absorption of satisficing, participants are free to select non-satisficing sales profiles. The results reveal that most participants are satisficers who tend to adjust aspiration levels if they cannot be satisfied.
Keywords: C92; C72; D43; 330; Satisficing behavior; Duopoly; Profit aspiration; Theory absorption; Duopol; Absatz; Beschränkte Rationalität; Test; Theorie; Nichtkooperatives Spiel